Like it! Maps as a Subject and a Springboard for discussion in social media - Nieścioruk Kamil (Polish Cartographical Review, 2020)
In the modern world of mass information being reduced to colourful images, maps have the chance to become a medium that transmits important information in an attractive format. Due to time pressure, many cartographic publications that have a short life span on the internet contain a lot of methodological errors. Viewers receive an image that is hard to interpret, incomplete or even incorrect. The author aims to summarize and classify the cartographic content of social media, while bearing methodology, the role of the cartographer and users’ reactions to that content in mind. The springboard to online discussion is mainly a map topic. Their design or methodology is of little interest in most cases. This may be due to insufficient knowledge of how forms (their correctness and quality) shape messages. Hence the role of the cartographer is important, what can be seen – among methodological remarks – as one of conclusions. It seems that map-makers are becoming more expert, and are guiding map lovers and amateur cartographers towards creating good, effective and elegant maps.